Sub‐3 nm particles observed at the coastal and continental sites in the United States. Issue 2 (27th January 2014) - Yu, Huan; Gannet Hallar, A.; You, Yi; Sedlacek, Arthur; Springston, Stephen; Kanawade, Vijay P.; Lee, Yin‐Nan; Wang, Jian; Kuang, Chongai; McGraw, Robert L.; McCubbin, Ian; Mikkila, Jyri; et al.
Abstract Direct measurements of atmospheric sub‐3 nm particles are crucial for understanding the new particle formation mechanisms, but such measurements are very limited at present. We report measurements of sub‐3nm particles at Brookhaven, New York (a coastal site in summer) and Kent, Ohio (a continental site in winter). During daytime, in approximately 80% of the observation days at both sites, sub‐3nm particle events were observed with concentrations of 2800 ± 1600 cm‐3, and they appeared with the elevated sulfuric acid concentrations. During the nighttime at the coastal site under the marine air mass influences, there were also substantial concentrations of sub‐3nm particles (1500 ± 400 cm‐3), but they did not grow larger. On the other hand, at the coastal Brookhaven site under the continental air mass influences and at the inland Kent site during the night, the sub‐3nm particles were significantly lower (190 ± 130 cm‐3). Our results indicate that sub‐3nm particles were not always present, and their presence was rather closely associated with specific aerosol nucleation precursors: sulfuric acid and other unknown condensable chemical species likely present in the marine air masses. These findings are thus different from other studies conducted in the Finland boreal forest, which showed a persistent presence of high concentrations of sub‐2nm particles and that these sub‐2nm particles were more correlated to monoterpene oxidation products than to sulfuric acid. Therefore, different nucleation mechanisms, as opposed on to a universal mechanism, involving different nucleation precursors dominate in different atmospheric environments with different emissions and transported trace gases.